Water quality dynamics and hydrology in nitrate loaded riparian zones in the Netherlands - Hefting, Mariet; Beltman, Boudewijn; Karssenberg, Derek; Rebel, Karin; van Riessen, Mirjam; Spijker, Maarten (Environmental pollution (1987), 2006)
Riparian zones are known to function as buffers, reducing non-point source pollution from agricultural land to streams. In the Netherlands, riparian zones are subject to high nitrogen inputs. We combined hydrological, chemical and soil profile data with groundwater modelling to evaluate whether chronically N loaded riparian zones were still mitigating diffuse nitrate fluxes. Hydraulic parameters and water quality were monitored over 2 years in 50 piezometres in a forested and grassland riparian zone. Average nitrate loadings were high in the forested zone with 87 g NO 3 −-N m −2 y −1 and significantly lower in the grassland zone with 15 g NO 3 −-N m −2 y −1. Groundwater from a second aquifer diluted the nitrate loaded agricultural runoff. Biological N removal however occurred in both riparian zones, the grassland zone removed about 63% of the incoming nitrate load, whereas in the forested zone clear symptoms of saturation were visible and only 38% of the nitrate load was removed. Riparian zones reduced nitrate from agricultural lands.